Advances in lead-free flexible piezoelectric materials for energy and evolving applications - Jacem Zidani; Latifa Tajounte; Abdellah Benzaouak; Noureddine Touach; Adam Duong; Moneim Zannen; Abdelilah Lahmar (Advanced Industrial and Engineering Polymer Research, 2025)
The review highlights the advancements in flexible lead-free piezoelectric materials, emphasizing their potential for energy harvesting and sustainable energy. Although normal piezoelectric materials such as lead zirconate titanate (PZT) have great efficiency, their lead content causes environmental issues. This research focuses on replacement materials like biodegradable polymers and bismuth sodium titanate (BNT), which not only show interesting piezoelectric capabilities but also have advantages in terms of flexibility and biocompatibility. In order to increase piezoelectric performance while maintaining flexibility, it is advised to include inorganic fillers into polymer matrices, therefore qualifying these materials for usage in biomedical and wearable electronics applications. The evaluation also covers the issues resulting from the great usage of these resources, including e-waste and the need of sustainable solutions. The general message of the research underlines the need of developing new piezoelectric materials able to effectively gather mechanical energy from different sources, therefore promoting self-sustaining systems and reducing reliance on traditional power sources. The review also underlines how lead-free piezoelectric materials can boost power density and chemical oxygen demand (COD) removal rates in microbial fuel cells (MFCs), therefore promoting sustainable energy solutions that turn organic waste into bioelectricity.